A nurse’s participation in psychiatric rehabilitation - Wilczewska, Lucyna; Ciszkowska-Kreft, Maria (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. This paper is an attempt to assess theoretical knowledge, participation and commitment in psychiatric rehabilitation of the nursing staff working in general psychiatrics departments of the Hospital for Patients with Nervous and Mental Disorders in Starogard Gdański. A considerable part of the investigated group were patients staying in general psychiatrics departments. Aim of the study. The objective of the paper is to analyze the patients’ needs and problems related to psychiatric rehabilitation and presenting the patients’ opinions on the nursing staff participation and commitment in this form of therapy. Material and methods. These investigations were carried out by means of two questionnaires with the use of the observation and interview method. The investigations comprised 95 persons with mental disorders staying in general psychiatrics departments and 70 nurses employed at these departments and taking care of the patients. Results and conclusions. As the investigation shows, the nursing staff has theoretical knowledge and addresses the patients’ needs and problems well. The staff does not always initiate actions in order to satisfy their patients’ needs and to solve their problems, whereas the patients are assessed as a group that cooperates with their therapeutic team but needs to be encouraged to it. The patients assess the work or the nursing staff well. However, they attribute a greater role in their therapy to doctors. What they expect most is support and information in the scope of pharmacotherapy. They think that they do not need psychoeducation and they assess themselves as active participants of psychiatric rehabilitation. Nursing Topics 2010; 18 (4): 483-489